Trends and emerging frontiers of mesenchymal stem cells in intervertebral disc degeneration: a bibliometric analysis (2000–2024) - Zhao, Jian; Li, Shuwen; Cheng, Jie; Xu, Xiang; Bai, Ming; Yu, Yingnan; Liu, Meixia; Yin, Heping; Wu, Yimin (Frontiers in Medicine, 2025)
BackgroundIntervertebral disc degeneration (IVDD) is a major global cause of disability, and mesenchymal stem cell (MSC) therapy offers a promising regenerative solution by targeting the root causes of degeneration, unlike conventional symptom-focused treatments. This bibliometric analysis explores trends and emerging research areas in MSC applications for IVDD.MethodsA comprehensive literature search was conducted in the Web of Science Core Collection database, covering publications from 2000 to 2024. Bibliometric and visualized analysis was performed using VOSviewers, CiteSpace and the R package “Bibliometrix.”ResultsThis bibliometric analysis reviewed 931 articles, revealing an overall upward trend in publication activity. Leading authors included Sakai Daisuke, Grad Sibylle, and Alini Mauro. China and the USA led in publication volume and citation counts, while the United Kingdom achieved the highest average citations per publication. The University of Pennsylvania and Zhejiang University were the most productive institutions. Key journals included Biomaterials, Spine, and Tissue Engineering Part A. Earlier core keywords primarily focused on foundational concepts such as “gene expression,” “articular cartilage,” “anulus fibrosus” and “extracellular matrix.” Recent keyword bursts include “activation,” “autophagy,” “extracellular vesicles,” “apoptosis,” “exosome,” and “oxidative stress.”ConclusionThis bibliometric analysis revealed key research focuses on foundational biological mechanisms, translational applications, and addressing specific challenges in the use of MSC for IVDD. Future research is likely to focus on optimizing MSC functionality, developing cell-free therapies such as extracellular vesicles, and targeting the molecular mechanisms involved in disc degeneration and regeneration.